GHOSTING DALAM PEMBELAJARAN ONLINE: SEBUAH PERSPEKTIF DARI SISI TUTOR - Dyah Aniza Kismiati; Ucu Rahayu; Mery Novianti; Zakirman; Yos Sudarso (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
The Covid-19 pandemic caused many significant changes in the learning system. By the implementation of online learning policies, it raises its own problematics until the emergence of ghosting phenomena in learning. The ghosting phenomenon is seen as the inactivity of students in online learning. This study is a type of quantitative descriptive research using survey method with a sample of 1,974 tutors at the Open University. The data was collected through questionnaire instruments shared online with tutors. The questionnaire instrument is an open question and there is also a likert scale. As a support, also conducted interviews with several tutors. The sampling technique used is a random sampling technique. The results of this study inform that 94.43% of tutors have experienced the phenomenon of ghosting carried out by students while 5.57% stated that there is no ghosting phenomenon in online learning. Of the 94.43% who stated the occurrence of the ghosting phenomenon, 31.05% of them think that ghosting is a phenomenon of student inactivity in online learning (not responding when called and invited to discuss), 20.62% of other tutors believe the same thing even admits that the ghosting phenomenon is common in online learning, other tutors also revealed some things related to ghosting in online learning. Thus, learning strategies are needed to overcome the phenomenon of ghosting in online learning.